2010
DOI: 10.1371/journal.pone.0011359
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Mouse Neuroethology in the Laboratory Environment

Abstract: In this report we demonstrate that differences in cage type brought unexpected effects on aggressive behavior and neuroanatomical features of the mouse olfactory bulb. A careful characterization of two cage types, including a comparison of the auditory and temperature environments, coupled with a demonstration that naris occlusion abolishes the neuroanatomical changes, lead us to conclude that a likely important factor mediating the phenotypic changes we find is the olfactory environment of the two cages. We i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 38 publications
2
22
0
Order By: Relevance
“…The present results indicate that during plastic responses to chronic odorant exposure, supernumerary glomeruli are added and consolidated as the olfactory bulb matures; no glomerular elimination was seen under any experimental condition (Figure 3 and S3). This result is compatible with the idea that at least under chronic odorant exposure before, during or after glomerular formation, the olfactory bulb uses a constructivist strategy, both at the circuit and glomerular levels, to respond to increased sensory demands; however, this process did not involve an increase of total glomerular volume (Figure 2 and S4); also see [14], [39]. In summary, the present results document a new strategy for the developing olfactory bulb to engange plastic responses.…”
Section: Discussionsupporting
confidence: 87%
“…The present results indicate that during plastic responses to chronic odorant exposure, supernumerary glomeruli are added and consolidated as the olfactory bulb matures; no glomerular elimination was seen under any experimental condition (Figure 3 and S3). This result is compatible with the idea that at least under chronic odorant exposure before, during or after glomerular formation, the olfactory bulb uses a constructivist strategy, both at the circuit and glomerular levels, to respond to increased sensory demands; however, this process did not involve an increase of total glomerular volume (Figure 2 and S4); also see [14], [39]. In summary, the present results document a new strategy for the developing olfactory bulb to engange plastic responses.…”
Section: Discussionsupporting
confidence: 87%
“…As suggested above, the differences between these and our studies could be due to differences in the strain, age and/or BrdU injection protocol. In addition, a recent report indicated that behavior can be greatly influenced by environmental conditions, making comparison across behavioral studies more difficult (Oliva et al, 2010). Nevertheless, further studies are necessary to determine whether activation of V2R sensory neurons in the VNO by social odors and concomitant activation of the pAOB promotes neurogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Mice were bred and housed in static micro-isolation cages. A previous study in our laboratory examined two types of caging/housing environments to determine the effects of environment on olfactory function (Oliva et al, 2010). High ventilated caging mechanically exchanges fresh air at a rate of one volume per minute.…”
Section: Methodsmentioning
confidence: 99%
“…Low ventilation or static micro-isolation cages passively exchange air through a filter cover. Oliva et al (2010) noted differences in mouse behavior (e.g., an increase in intermale aggression when housed in “standard”, high ventilated caging) as well as neuroanatomical changes that occurred in the OB as a result of the differences in housing conditions. Therefore, this study housed all mice in static micro-isolation cages.…”
Section: Methodsmentioning
confidence: 99%